DC SHOCK SIMULATOR - Muhammad Amir Maruf; Bambang Guruh Irianto; Tri Bowo Indrato (Journal of Electronics, Electromedical Engineering, and Medical Informatics, 2019)
Defibrillators are electronic devices that carry shock electrical signals (pulses) to the heart muscle to maintain myocardial depolarization that is undergoing cardiac fibrillation (ventricular fibrillation or atrial fibrillation) (Bronzino, 2000). There are several conditions that must be met for the occurrence of shock processes including shock time, energy to be provided, patient and operator safety. In this defibrillator the use of selectors / energy selection is linear in the range 1-30 Joules with the use of tools at 10, 15, 20, 25, 30 Joules. The energy will then be discarded or given to the patient via a paddle when pressed the Discharge / shock button. The result of the signal given to the patient is monophasic. This study used a pre-experimental type with a One Group post test design research design. Measurements were made 5 times the volt meter at the test points determined by the compiler.